2016
DOI: 10.1016/j.ijhydene.2016.02.144
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive simulations of cavity-based detonation in supersonic hydrogen–oxygen mixture

Abstract: Two-dimensional reactive Euler equations with a detailed reaction modelwhere the molar ratio of the combustible mixture H2/O2/Ar is 2:1:7 under the condition of pressure 6.67 kPa and temperature 298 K, are solved numerically with adaptive mesh refinement method to investigate detonation combustion using a hot jet initiation in cavity-based channels filled with the supersonic combustible mixture.Results show that from the comparison between the simulations in a cavity-based channel and a straight channel withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…The Mach detonation reflection, which serves as a strong ignition source, contributes significantly to the realization of a complete detonation initiation in the whole channel. In the previous work [28], when the incoming velocity is given as the CJ velocity, the detonation front is almost sustained at the same location upstream in the cavity after the hot jet is shut down due to cavity oscillation. It is suggested that, for a successful detonation wave interaction with cavity, the incoming flow velocity should be higher than the corresponding CJ velocity to ensure downstream propagation of detonation after the hot jet shutdown.…”
Section: Results and Analysismentioning
confidence: 88%
See 2 more Smart Citations
“…The Mach detonation reflection, which serves as a strong ignition source, contributes significantly to the realization of a complete detonation initiation in the whole channel. In the previous work [28], when the incoming velocity is given as the CJ velocity, the detonation front is almost sustained at the same location upstream in the cavity after the hot jet is shut down due to cavity oscillation. It is suggested that, for a successful detonation wave interaction with cavity, the incoming flow velocity should be higher than the corresponding CJ velocity to ensure downstream propagation of detonation after the hot jet shutdown.…”
Section: Results and Analysismentioning
confidence: 88%
“…The hot jet is set to the equilibrium CJ state of a H 2 ∕O 2 mixture with a stoichiometric molar ratio under the condition of pressure 6.67 kPa and temperature 298 K [28]. To model the sonic injection in experiments, the injection velocity of the jet is set to the local sonic speed to make it a chocked one.…”
Section: Computational Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed process of detonation initiation using a hot jet in a cavity-embedded channel has been illustrated previously in detail [28], where the velocity of the supersonic incoming flow is given as the corresponding V CJ . To have a quick understanding of this issue, a very brief introduction is provided here.…”
Section: Results and Analysismentioning
confidence: 99%
“…In addition, it is expected that the DDS can be suitable for higher flight Mach numbers than the 3 conventional scramjet. Based on this idea, we have conducted a series of numerical simulations [5][6][7][8] on detonation combustion in supersonic combustible mixtures using a hot jet initiation. The adaptive mesh refinement open-source program AMROC (Adaptive Mesh Refinement in Object-oriented C++) [9][10][11] based on the Structured Adaptive Mesh Refinement (SAMR) approach [12][13] had been adopted to solve the reactive Euler equations with simplified [14] and detailed reaction models [15] using a robust second-order accurate MUSCL-TVD scheme.…”
Section: Introductionmentioning
confidence: 99%